2019
DOI: 10.15314/tsed.491662
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Decision-Making Skills of the High School Students Participating in School Sports Activities

Abstract: The aim of this study is to identify the decision-making skills of the high school students participating in school sports activities. The sample of the study consisted of 221 (n=96 girls and n=125 boys) volunteer students studying in 4 different high schools affiliated to Kırıkkale Provincial Directorate of National Education in 2017-2018 academic year. The students participating in the study were divided into 3 different age groups. 49.3% (n=109) of the students are in the 14-15 age group, 35.7% (n=79) are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As a result of this change, it was concluded that disabled individuals should be directed to sports in order to facilitate their adaptation to society (DUNN; FAIT, 1997;SEVINDI, 2002). Because sports play an active role in providing emotional satisfaction, quality of life, creating a social environment, freedom, decision-making skills, self-confidence development, self-knowledge and reaching the targeted goal (AVCI; CAN, 2020;KARAKULLUKÇ;ÖÇALAN;AVCI, 2019). At the same time, sports cardio offers a high perceived quality of life, self-confidence, and high self-efficacy for individuals with disabilities, in addition to its main benefits for metabolic fitness (CHERI BLAUWET;STUART;WILLICK, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this change, it was concluded that disabled individuals should be directed to sports in order to facilitate their adaptation to society (DUNN; FAIT, 1997;SEVINDI, 2002). Because sports play an active role in providing emotional satisfaction, quality of life, creating a social environment, freedom, decision-making skills, self-confidence development, self-knowledge and reaching the targeted goal (AVCI; CAN, 2020;KARAKULLUKÇ;ÖÇALAN;AVCI, 2019). At the same time, sports cardio offers a high perceived quality of life, self-confidence, and high self-efficacy for individuals with disabilities, in addition to its main benefits for metabolic fitness (CHERI BLAUWET;STUART;WILLICK, 2012).…”
Section: Introductionmentioning
confidence: 99%